2015
DOI: 10.1039/c5cp01730k
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous ion and neutral evaporation in aqueous nanodrops: experiment, theory, and molecular dynamics simulations

Abstract: We use a combination of tandem ion mobility spectrometry (IMS-IMS, with differential mobility analyzers), molecular dynamics (MD) simulations, and analytical models to examine both neutral solvent (H2O) and ion (solvated Na + ) evaporation from aqueous sodium chloride nanodrops. For experiments, nanodrops were produced via electrospray ionization (ESI) of an aqueous sodium chloride solution. Two nanodrops were examined in MD simulations: a 2,500 water molecule nanodrop with 68 Na + and 60 Cl -ions (an initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 64 publications
(129 reference statements)
2
38
3
Order By: Relevance
“…The scaling of the data implies that the observation of the single-ion ejection from a minute nanodrop does not warrant an IEM mechanism. Our view is different from that that has been presented in the literature 80,81 where the ejection of simple ions from droplets composed of ≈ 1000 H 2 O is considered evidence of the ion evaporation mechanism (in the sense of Iribarne-Thompson and Labowsky et al). We elaborate more on this point in the next section.…”
Section: Ejection Mechanismcontrasting
confidence: 96%
See 3 more Smart Citations
“…The scaling of the data implies that the observation of the single-ion ejection from a minute nanodrop does not warrant an IEM mechanism. Our view is different from that that has been presented in the literature 80,81 where the ejection of simple ions from droplets composed of ≈ 1000 H 2 O is considered evidence of the ion evaporation mechanism (in the sense of Iribarne-Thompson and Labowsky et al). We elaborate more on this point in the next section.…”
Section: Ejection Mechanismcontrasting
confidence: 96%
“…Higashi et al have found excellent agreement 80 of MD evaporation simulations at T = 460 K with the IEM Labowsky et al model. 25 The simulated droplets comprise 2500 and 1000 water molecules with a mixture of Na + and Clions at a super-saturation.…”
Section: Limitations Of Atomistic Simulations In Detecting the Iemmentioning
confidence: 82%
See 2 more Smart Citations
“…The monomer and dimer of the THABr are separated by another small peak (at 418 Volts) more 'visible' in the Figure 3B in which the CPC is used as detector thanks to its sensitivity. This peak appears when the DMA is working in closed loop without dryer to remove volatile solvent (methanol, ethanol or acetonitrile) vapors introduced in the sheath gas by the droplets produced in the electrospray source [24,49,50]. That small peak is produced by the solvated monomer of the THABr with these vapors and eventually water vapor in case the carrier gas used through the electrospray source is not dry N 2 or air from a cylinder.…”
Section: Resultsmentioning
confidence: 99%